5x-6=3x-6+2x

Simple and best practice solution for 5x-6=3x-6+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-6=3x-6+2x equation:


Simplifying
5x + -6 = 3x + -6 + 2x

Reorder the terms:
-6 + 5x = 3x + -6 + 2x

Reorder the terms:
-6 + 5x = -6 + 3x + 2x

Combine like terms: 3x + 2x = 5x
-6 + 5x = -6 + 5x

Add '6' to each side of the equation.
-6 + 6 + 5x = -6 + 6 + 5x

Combine like terms: -6 + 6 = 0
0 + 5x = -6 + 6 + 5x
5x = -6 + 6 + 5x

Combine like terms: -6 + 6 = 0
5x = 0 + 5x
5x = 5x

Add '-5x' to each side of the equation.
5x + -5x = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| ln(8x)=3.9 | | 3t+7=3t+6 | | 5h^2+8h-85=0 | | (Y-9)-(Y+3)=5Y | | 13x-3x=2x+3 | | 5x=10-3[2x-5(x+8)] | | (Y-7)-(Y+4)=10Y | | 6x+11=12-7x | | X+2x=50+90+10 | | p-10=-10 | | y-3=6(x+1) | | 3(4m-5)=124m | | 2*x+1=2+2x | | (15b-1)-7(2b+2)=-6 | | 7x+4x+3+9=6x+3+4x | | x+7*2=3x+5 | | 10b+3+4= | | 12-7x=6x+11 | | 96+122=180 | | x+(x-48700)=284790 | | f(4)=10-.25*4 | | -9+5x=-9 | | 7x+5=7-7x | | 6x+12=-28-4c | | 7x^2+6=17x-5 | | 6x+9+7y-2x+3= | | 8+6x=-22+x | | 4x-8+3x=60-2x+3x | | t*4-4=11 | | P^2=5p+84 | | 10y-3=8y+7 | | x+88+127=180 |

Equations solver categories